A sociological and narrative methodology to analyse photographic stories - Visa Barbosa, Mariona (Estudios sobre el Mensaje Periodístico, 2012)
This paper exposes the methodology used to realize a sociological and semiotic-narrative analysis of the family albums. From a corpus that includes 40 albums sine the 60s up to the current days, a multidisciplinary analysis is done, which reflects the evolution of our society in the change in familiar roles and the values. In turn, the narrative analysis shows the change in the way we explain the history of our life through the photographs. The used methodology is therefore basically pragmatic and besides the described disciplines it contains a technological, semiotic and compositive perspective.
Keywords: photography; familiar album; sociology; storytelling